THE RELATIONSHIP OF RELIGIOUS STRUGGLE WITH EXPERIENCED EMOTIONS, EMOTION REGULATION SKILLS AND SELF-RATED PHYSICAL HEALTH IN A SAMPLE OF LATVIAN CHRISTIANS - Putniņa, Laila; Trups-Kalne, Ingrīda; Lietaviete, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Studies to date have linked religious struggle to poorer health outcomes. The present study aims to investigate the relationship between religious struggle, emotions, emotion regulation skills, and self-rated physical health and to search for possible mediating variables explaining this relationship. The study examined the mediating role of negative emotions and emotion regulation skills in the association of religious struggle with health outcomes in a sample of Latvian Christians. The study involved 306 participants aged between 16 and 74, belonging to different Christian denominations. Instruments used for data collection include the Religious and Spiritual Struggle (RSS) Scale, Emotion Regulation Skills Questionnaire (ERSQ), and The Physical Health Questionnaire (PHQ). The results of the study demonstrated an association between religious struggle and poorer health outcomes and confirmed the mediating role of negative emotions and emotion regulation skills in these relationships. Emotion regulation skills are associated with a higher frequency of positive emotions and better health outcomes. The findings from this study could help in designing more effective interventions for individuals experiencing religious struggle in crisis situations.